2019
DOI: 10.1186/s12885-019-5706-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between opportunistic and organised breast cancer mammography screening in the Swiss canton of Fribourg

Abstract: Background Breast cancer screening mammography is widespread in industrialised countries within the framework of public health program or opportunist form. Only few data exist on the comparison of effectiveness between organised and opportunistic screening. The aim of this study is to compare organised and opportunistic screening using population-based data from the Fribourg cancer registry, Switzerland. Methods We included all first primary breast adenocarcinoma diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…Our findings on higher rates of having a mammogram among women living in cities compared to villages are in line with other studies [33,34]. However, a study carried out in Korea showed the opposite result: a rural residence was related to higher rates of BC screening attendance [19].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on higher rates of having a mammogram among women living in cities compared to villages are in line with other studies [33,34]. However, a study carried out in Korea showed the opposite result: a rural residence was related to higher rates of BC screening attendance [19].…”
Section: Discussionsupporting
confidence: 91%
“…This study showed a significant difference between the opportunistic screening and diagnostic patients in terms of the axillary involvement (p = 0.009), stage of the cancer (p < 0.001), DCIS detection rate and mean tumor size which are the main benchmarks of a better outcome. A recent study evaluating the opportunistic screening showed its efficacy with a reduced mortality which was comparable to population-based screening outcomes [12]. Although our study does not provide its effect on mortality our screening results are comparable with the populationbased screening of BBCSP and showed significant differences compared to diagnostic patients.…”
supporting
confidence: 76%
“…Compared to BBCSP results we had a relatively lower percentage of stage 0 and 1 cancer but higher than the national data. A recent study showed similar findings with a lower DCIS detection rate in the opportunistic screening group compared to population-based organization [12]. They have explained this difference with a possible more effective evaluation of the mammograms in organized screening programs by specifically trained screening radiologists.…”
Section: Discussionsupporting
confidence: 53%
“…It leads to unnecessary expense and is also potentially harmful: use of X-rays for BCS, and unnecessary anxiety and needless treatments for both BCS and CCS. [23][24][25] Obese and overweight women underwent more BCS than CCS, as seen clearly in pattern A. This finding is partly explained by their lower socioeconomic position because BCOS is free in contrast to CCS: the cost of a Pap test is added to the cost of the office visit.…”
Section: Discussionmentioning
confidence: 99%
“…Overscreening was concentrated in patterns C and D for CCS and in pattern D for BCS (due to the regular use of BCOpS). It leads to unnecessary expense and is also potentially harmful: use of Xrays for BCS, and unnecessary anxiety and needless treatments for both BCS and CCS [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%